Metaphysics of laughter in Nineteenth-century philosophical discourse. Moland, L. (Ed.). (2018). All Too Human. Laughter, Humor, and Comedy in Nineteenth-Century Philosophy. Boston: Springer. - Stoliar, Maryna (Sententiae, 2020)
Review of Moland, L. (Ed.). (2018). All Too Human. Laughter, Humor, and Comedy in Nineteenth-Century Philosophy. Boston: Springer.